Alginate–Poly[2-(methacryloyloxy)ethyl]trimethylammonium Chloride (PMETAC) Immunoisolating Capsules Prolong the Viability of Pancreatic Islets In Vivo - Polina Ermakova; Ekaterina Vasilchikova; Arseniy Potapov; Maxim Baten’kin; Liya Lugovaya; Alexandra Bogomolova; Julia Tselousova; Alexey Konev; Natalia Anisimova; Alena Egoshina; Mariya Zakharina; Nasipbek Naraliev; et al. (Biomedicines)
Background/Objectives: This study focuses on the development and evaluation of novel alginate–poly[2-(methacryloyloxy)ethyl]trimethylammonium chloride (PMETAC) microcapsules for encapsulating pancreatic islets to address insulin deficiency in diabetes. Methods: In previous research, we fabricated and characterized PMETAC microcapsules, evaluating their stability and permeability in vitro. This study further probes the capsules in vivo, focusing on the functional activity of the encapsulated islets post-transplantation, their viability extension, and the assessment of the immunoprotective, antifibrotic properties, and biostability of the capsules. Results: Rabbit-derived islets were encapsulated and transplanted into diabetic rats. The encapsulated islets maintained insulin secretion for up to 90 days, significantly longer than non-encapsulated ones, which ceased functioning after 7 days. Histological analysis demonstrated high biocompatibility of the PMETAC coating, resulting in minimal fibrotic overgrowth around the capsules. Conclusions: The study highlights the critical role of immunoprotection and the tendency to reduce fibrosis in prolonging islet function. These findings suggest that PMETAC-coated capsules offer a promising solution for cell-based therapies in diabetes by improving graft longevity and reducing fibrotic overgrowth.